IMPACT OF ADOPTION OF IMPROVED RICE PRODUCTION TECHNOLOGIES ON YIELD AND INCOME OF COOPERATIVE SOCIETIES’ FARMERS IN BAUCHI AND GOMBE STATES, NIGERIA - Babaji, A.U.; Abu, I.A.; Murtala, N.; Ochi, J.E. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study was examined the impact of adoption of improved rice production technologies on yield and income of cooperative societies’ farmers in Bauchi and Gombe States, Nigeria. A multi-stage sampling procedure was used to select 524 respondents comprising of 262 members and 262 non-members from both States. Data were collected using structured questionnaires and analysed using descriptive and inferential statistics. The results showed that, the mean age of the respondents was 41years for the members and non-members in Bauchi State, while 41 and 42 years were the mean age in Gombe State for both categories of the respondents respectively, with the mean farming experience of 7 and 12 years in Bauchi State, while 9 and 10 years in Gombe State for both the members and non-members respectively. The results showed a significant difference (P<0.05) between the mean household size among members and non-members in Bauchi State as the calculated Z-value (2.94) is higher than the tabulated Z-value (1.96). The trend was also similar in Gombe State where there was a significant difference (P<0.05) between the mean household size among members and non-members as the calculated Z-value (2.70) is also higher than the tabulated Z-value (1.96). The results showed no significant difference (P<0.05) between the mean farm size among members and non-members in Bauchi State as the calculated Z-value (0.63) is lower than the tabulated Z-value (1.96). The trend wasn’t similar in Gombe State which showed a significant difference (P<0.05) between the mean farm size among members and non-members as the calculated Z-value (4.80) is higher than the tabulated Z-value (1.96). education level, sex and rice farming experience were found to be positively significant (P<0.001) while extension visit was found to be positively significant (P<0.05) in predisposing adoption improved rice production technologies (IRPTs) among members and non-members of rice cooperative societies in the study area. The results from the Nearest Neighbor Matching (NNM), radius Matching Method (RMM), Stratification Method (SM) and Kernel Matching Method (KMM) indicate that the adoption of IRPTs had significant positive impact on income and yield among members compared to non-members (P˂0.01). It was concluded that the adoption IRPTs have significant impact on yield and income of members of cooperatives societies compared to their counterparts. The study therefore recommends that, farmers should form formidable cooperative societies so as to enjoy economies of scale in pooling their resources to purchase farm inputs.